Cognitive and Structure-Proposition-Evaluation Strategies in Teaching TOEFL Reading Comprehension to High Low Motivated Students - Ekadini, Lulu'; Rukmini, Dwi (Universitas Negeri Semarang, 2018)
The present study investigated the effectiveness of Cognitive and Structure-Proposition-Evaluation strategies in teaching TOEFL reading comprehension to high and low motivated students. An experimental research with factorial design 2x2 was used in this research. The first group was treated by using cognitive strategy and the other was treated by using SPE strategy. The motivational questionnaire was conducted for classifying the students upon the high and low motivation. The data were analyzed by applying Two-Way ANOVA. The result reveals that (1) cognitive strategy had a significant effect for teaching TOEFL reading comprehension among students with high and low motivated students, (2) SPE strategy had a significant effect for teaching TOEFL reading comprehension among high and low motivated students, (3) there was no significant difference between the students’ achievement after the implementation of cognitive and SPE strategies for teaching TOEFL reading comprehension among high and low motivated students, (4) there was no significant difference of students’ motivation in reading comprehension when they are taught by using cognitive and SPE strategies for high and low motivated students, (5) there was no interaction among teaching strategies (cognitive and structure-proposition-evaluation strategies), motivation (high and low motivated students), and students’ reading comprehension.